Sweetened Drink Consumption Pattern and Risk of Obesity Awareness - Erma Wahyu Mashfufa; Alvina Khotijah; Lilis Setyowati; Navy Sealsi Adinda Prisca Marina; Ollyvia Freeska Dwi Marta (Jurnal Keperawatan, 2022)
Introduction: Trends in sweetened drink consumption increased in the past two years. The ease of technology to order food and beverage through online applications and the increasing number of cafes provide a comfortable place, causing a change in lifestyle and eating patterns whose nutritional value does not meet health standards. Excessive calorie intake will have an impact on health, causing obesity. Objectives: To explore the pattern of sweetened drink consumption and awareness of the risk of obesity among nursing students. Methods: A cross-sectional study was conducted for three months (June-September 2021). We recruited 88 nursing students. Using the Indonesian version of the Beverage Frequency Questionnaire (BFQ), we collected the data and the obesity knowledge questionnaire by purposive sampling. Total intake of drink in milliliter and calories in kcals were calculated. The data were analyzed through SPSS version 23. Result: Most nursing students' consumption of sweetened drinks was in the high category, with 75 respondents (85%) and 13 respondents (15%) in the normal category. The drinks most often consumed were tea, instant coffee, and flavored milk. Body mass index (BMI) was mainly in the normal category with 47 respondents (53%), 27 respondents (31%) in the fat category, and 14 respondents (16%) in the thin category. Awareness of the risk of obesity, most respondents 72 respondents (81%) have good knowledge of 72 respondents (81%). The respondents' average daily consumption of sweetened drinks was 113 grams per day. Conclusion: The majority of respondents have a high consumption pattern of sweetened drinks even though they have normal nutritional status and are aware of the risk of obesity.